The Relationship between Management Information Systems Based on Rapor Digital Madrasah (RDM) and the Quality of Madrasah Education - Ma'ruf, Muh. Arif; Munaya, Amira; Imtiyazi, R. Naila; Slamet, Cepy (IAIN Ponorogo, 2023)
This paper investigates the relationship between madrasah digital report card-based management information systems and madrasah education quality at Madrasah Aliyah Al-Masthuriyah Sukabumi. Education management information systems are essential in managing educational institutions, especially schools. It is for effectiveness, efficiency and accuracy to improve school quality. This research utilises a quantitative descriptive methodology in order to objectively describe the relationship between variables. The data were collected through questionnaires, observation, and documentation. The researchers found that the relationship between the management information system based on the Rapor Digital Madrasah (RDM) and the Quality of Madrasah Education has a significant relationship with a sig. correlation value of 0.497. The higher the management information system based on RDM, the higher the Madrasah Education Quality. Then, looking at the coefficient of determination means that the contribution of the variable management information system based on the RDM to the Quality of Madrasah Education is 24.7%; other factors influence the rest.